EFFECT OF FERTILIZATION ON GROWTH CHARACTERISTICS OF CYPRINUS CARPIO CULTURED IN RICE FIELDS IN IRAQ - Mohammed A.M.,; M. S. Al-Khshali, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was carried out to evaulate the effect of organic fertilization on the growth of common carp Cyprinus carpio cultured in rice fields and its effect on rice production as well as the possibilitd reducing the feed provided to fish. Four fields with an area of 100 m2 were cultured Yasmine rice represented four treatments. Common carp fish were cultured in it with a weight of 100 g/fish and a culture density of 100 fish/field. In the first treatment, organic manure was added without providing fish feed, second treatment, organic manure was added with fish feed, the third treatment without adding organic manure with fish feed, and the fourth treatment without adding organic manure and without providing fish feed. The results of the statistical analysis rate showed that T2 showed a significant increased(p≤0.05) in relative and specific growth in T2 compared to all treatments followed by T3. The results of the statistical analysis of the characteristics of the rice yield showed the number of dahlias, number of grains / dahlia, weight of 1000 grains and grain yield, showed a significant difference (p≤0.05) in T2 and T3 compared to T1and T4, while there were no significant differences(P>0.05) between treatments for the weight of 1000 grains trait. the study concluded that it is possible to apply the fish farming system in rice fields in Iraq by using organic fertilization (cow waste) and adding supplementary feed, as the T2 treatment gave the best growth for fish and rice.